Deciphering microbial carbon substrates in PAH contaminated sediments using phospholipid fatty acids, and compound specific δ13C and Δ14C - Morrill, Penny L.; Szponar, Natalie; Johnston, Mathew; Marvin, Chris; Slater, Gregory F. (Organic Geochemistry, 2014)
Stable and radiogenic carbon isotopes (δ13C and Δ14C) of organic compounds and phospholipid fatty acids (PLFAs), as well as polycyclic aromatic hydrocarbon (PAH) ratios were used to determine sources and fates of organic contaminants in highly contaminated, and less contaminated sediments of Hamilton Harbour. The highly contaminated sediments had an order of magnitude more total petroleum hydrocarbons (TPHs) compared to the less contaminated sediments. The TPHs extracted from both sites were depleted in 14C (average Δ14C of −775‰ and −973‰, for Sites 1 and 2, respectively) consistent with inputs of fossil derived contaminants. Fossil carbon also contributed to the unextractable residue (Δ14C = −503 ± 55‰) in the sediment at the highly contaminated site relative to the less contaminated site (Δ14C = −132 ± 2‰) indicating inputs of fossil carbon not derived from petroleum or PAHs. Diagnostic PAH ratios (e.g. PAH:NaP between 0.01 and 1), and less negative δ13C (−25.6 ± 0.2‰) of the unextractable residue indicated that a coal derived source was the most likely source of these inputs. Despite the presence of this fossil carbon, there was little evidence of utilization of ancient carbon by the microbial community. The Δ14C of PLFAs from the highly contaminated site were slightly more 14C depleted (Δ14C = −138 ± 20‰) relative to the PLFAs from the less contaminated site (Δ14C = −77 ± 42‰), demonstrating some microbial metabolism of older carbon; however, the majority of the carbon metabolized was modern at both sites, indicating that there was minimal natural attenuation via bioremediation of fossil fuel organic contaminants.